DIGITAL LITERACY: THE URGENCY OF DIGITAL SKILL IMPROVEMENT THROUGH E-MODULES - Kuncahyono; Dian Fitri Nur Aini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe the implementation of digital literacy using e-modules and to increase the understanding of PGSD students. The type of this study was Classroom Action Research (CAR). The subjects of this study were students of PGSD Universitas Muhammadiyah Malang class of 2016, totaling 50 students. The implementation of digital literacy skills using e-modules used 3 learning stages, namely: (a) software engineering; (b) instructional design; and (c) the level of visual communication. Sources of data in this study were students' work in developing students active learning (SAL) oriented teaching materials, and the process of how students develop teaching materials by using student active learning (SAL) oriented e-module guidelines in elementary schools. Sources of data in this study were the SAL-based teaching materials designed by the students, and the process of developing teaching materials using student active learning (SAL) oriented emodule guidelines in elementary schools. The results of the study showed that students' understanding of digital literacy skills included: 1) The use of SAL-based e-module guidelines improved students' skills in compiling digital teaching materials. 2) The increase in students’ skills in compiling digital teaching materials after using the e-module guidelines was marked by the increase in student skills in compiling digital teaching materials from 56.8% to 82.5%. It can be said that using e-module guidelines improved the students’ skills in making digitalbased teaching materials.